(untitled) (Advances in Civil and Architectural Engineering, 2021)
This study considered the problem of understanding and use of risk management methods in construction projects and their representation in the literature and their practical application. Research of trends in risk management was conducted using studies from the EBSCO database that were published in the period from 1999 to 2015. The focus included the development of two terms, namely traditional and holistic approach to risk management as well as to uncertainty and opportunity management. The trend of leading standards in the field of project management, PMBoK and ISO 31000 indicated full support for the modernization of risk management that focused on the risks as well as potential opportunities in the project. The findings also revealed that the global practices continued to lack awareness of risk management and its benefits for project goals. A similar situation was found in Croatia by observing project management practices in two case studies, namely Project Zagrebačka obala in Rijeka and a Project of SEECEL Zagreb. Primarily, the lack of education and communication between experts are important issues requiring attention in practice and academics. It is necessary to gradually introduce standards over time to prepare for progress in managing uncertainties and adopting more holistic approaches.